Exploring Customer Satisfaction in Addition Apotek Services in Banjarbaru: The Role of Product Involvement, Brand Familiarity, and Consumer Attitudes - Siti Nur Faijah; Nurhayati Nurhayati (Eduvest - Journal of Universal Studies, 2025)
Customer satisfaction is a condition where customers feel satisfied or happy with the products or services they receive from a company. Improving customer satisfaction services, especially in pharmaceutical businesses such as pharmacies, does not escape the role of product involvement. Apart from the factors related to the products being sold, brand familiarity factors can also provide customer satisfaction when shopping. Apart from these two factors, there is a factor that is no less important, namely consumer attitudes. The phenomenon of consumer attitudes plays an important role in influencing customer satisfaction. This research aims to analyze and test the influence of product involvement, brand familiarity, and consumer attitudes on customer satisfaction. In achieving this goal, this research applies descriptive statistical analysis methods using SEM techniques with the help of SmartPLS software. Based on the results of the analysis, it can be concluded that the three independent variables, namely Product Involvement, Brand Familiarity, and Consumer Attitudes, have a significant and positive influence on Customer Satisfaction[A1]. This research contributes to developing effective customer satisfaction strategies in pharmaceutical retail, providing insights for pharmacy management to optimize service quality through enhanced product involvement, strengthened brand recognition, and positive consumer attitude formation, ultimately supporting sustainable business growth and competitive advantage in the healthcare sector.